2021
DOI: 10.1097/gme.0000000000001864
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the different subtypes in menopausal symptoms among middle-aged women in China: a latent class analysis

Abstract: Objective: Many studies have focused on the severity and prevalence of menopausal symptoms among middle-aged women, which are limited by heterogeneity and diversity of subtypes. Subtyping facilitates the adaptation to prevention and clinical intervention strategies that target women. To determine the existence of significant subgroups of women with similar menopausal symptoms, a person-centered approach was used to identify potential profiles of women during the menopausal transition. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 41 publications
(84 reference statements)
1
9
0
Order By: Relevance
“…To our knowledge, this is first study that has looked at patterns of a broad range of recurring symptoms in women in early adulthood. Although not directly comparable due to differences in the characteristics of study populations, symptom lists and timeframes over which symptoms are reported, our finding of a latent class with minimal symptoms and a latent class with many symptoms is consistent with studies of symptom patterns in populations of both men and women across broad age groups [ 5 , 39 ], women in mid-life [ 7 , 13 ], and cancer patients [ 40 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…To our knowledge, this is first study that has looked at patterns of a broad range of recurring symptoms in women in early adulthood. Although not directly comparable due to differences in the characteristics of study populations, symptom lists and timeframes over which symptoms are reported, our finding of a latent class with minimal symptoms and a latent class with many symptoms is consistent with studies of symptom patterns in populations of both men and women across broad age groups [ 5 , 39 ], women in mid-life [ 7 , 13 ], and cancer patients [ 40 ].…”
Section: Discussionsupporting
confidence: 75%
“…Latent class analysis of somatic symptoms in a Danish population found that women had a higher probability than men of being in classes with many symptoms compared with the class characterised by no symptoms [ 5 ]. Latent class analysis has been used to identify symptom patterns in women; however, these studies have either focussed on narrow groups of symptoms (e.g., menopausal [ 6 , 7 ], mood [ 8 ], menstrual and mood [ 9 ]), symptom patterns among women with specific conditions (e.g., dysmenorrhea [ 10 ], irritable bowel syndrome [ 11 ]) or women in midlife (i.e., during menopause transition) [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Literature shows that ethnic minority women may present with symptoms of menopause that are different, or described differently, to their white peers 1,2,3,4,5 . Our study has shown a communication gap in the consultation, rising from lack of awareness of peri/menopausal symptomatology in some ethnic minority women which does not allow them to advocate for their health, compounded by a lack of knowledge or confidence in some primary care clinicians to interpret and connect symptom presentation with a holistic menopause care lens.…”
Section: Discussionmentioning
confidence: 99%
“…The menopause is a natural stage in a woman's life, and each woman's experience is individual and unique. Research from the USA shows that different ethnic groups may have different experiences from their white peers, such as entering the peri/menopause at earlier ages 1 , having longer transition periods 2 , and emphasising different symptom experiences 3,4,5 . Acculturation and the stresses of poverty and structural racism appear to play a complex role in menopausal symptomatology, with recommendations to clinicians that ethnicity should be taken into account when interpreting symptom presentation 6,7,8,9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation